1973
DOI: 10.2170/jjphysiol.23.645
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Cardiac Output Related to Sex and Age

Abstract: Summary Maximum cardiac output (Qmax) was determined for 233 males (aged 9 through 53 years) and 102 females (aged 9 through 20 years) by the carbon dioxide rebreathing technique during bicycle exercise. Maximum cardiac output of the males progressively increased from 12.5 to 22.0 liter/min until age 17 through 18 years and was maintained at this level until age 24 years. From age 25 years a decrease in Qmax to 16.7 liter/min by age 53 years was observed. Qmax of the females increased from a level of 10.5 lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Indeed, Rowland et al (1997) reported an average increase in stroke volume above resting levels of 42% in boys and 26% in girls, in comparison to the 33% and 25% increase, respectively, found in the present study. The cardiac output, stroke volume, and heart rate values at maximal exercise reported by Miyamura and Honda (1973) in girls were remarkably similar to comparable results in the present study. On the other hand, values obtained in boys differed notably between the two series (Tables 2, 3), which could be due to differences in pubertal status or physical maturity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, Rowland et al (1997) reported an average increase in stroke volume above resting levels of 42% in boys and 26% in girls, in comparison to the 33% and 25% increase, respectively, found in the present study. The cardiac output, stroke volume, and heart rate values at maximal exercise reported by Miyamura and Honda (1973) in girls were remarkably similar to comparable results in the present study. On the other hand, values obtained in boys differed notably between the two series (Tables 2, 3), which could be due to differences in pubertal status or physical maturity.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac output in healthy children during exercise has been measured by several different techniques: CO 2 rebreathing (Bar-Or et al 1971;Gadhoke and Jones 1971;Godfrey et al 1971;Miyamura and Honda 1973;Turley and Wilmore 1997); inert gas uptake (Seely et al 1974); Doppler echocardiography (Rowland et al 1997(Rowland et al , 2000; or invasive techniques (Cumming 1977;Eriksson et al 1971). Godfrey et al (1971) provided reference values for stroke volume during upright exercise in a relatively large sample of children spanning the testable pediatric age range using the indirect Fick [CO 2 ] method.…”
Section: Introductionmentioning
confidence: 99%
“…Boys generally have greater maximal CO responses that girls [16], with CO max values of 12.5 L/min in 9-or 10-year-old boys vs 10.5 in similarly aged girls and 21.1 L/min in 19-or 20-year-old boys vs 15.5 in similarly aged girls [43]. These differences persist but are of lesser magnitude when CO max is indexed by body surface area.…”
Section: Gendermentioning
confidence: 92%
“…On the other hand, in cross-sectional studies Miyamura et al 23 , observed that the maximal cardiac output increased from 12.5 to 21.1 l/min in boys between ten and twenty years of age, respectively. According to Malina & Bouchard 2 , the dimensions of the heart increase over time until biological maturation along with body mass growth, and this enlargement is related to an elevation of both the stroke volume and cardiac output.…”
Section: Cardiac Outputmentioning
confidence: 92%
“…In fact, this variable presents smaller values for all relative intensity levels of exercise in the pediatric population 3,8,23 (Fig. 3).…”
Section: Cardiac Outputmentioning
confidence: 93%